Where are We Heading To; Conceptualising Nihilism and the LGBTQIA+ Community - Isaac, Oyagiri, Buduka; Apampa , Apampa Oluseyi; Osaro, Government Ntobari; Chinwendu, Agwuike (Journal of Ecohumanism, 2024)
This paper served as an exploratory investigation into two polarizing ideologies, Nihilism and LGBTQIA+. The study delves into the intricate interplay between the two concepts, employing perspectives from religious authorities, science, health, and the law of identity. Over the past few decades, society is inundated with persistent, victimizing and immoral struggles by perceived marginalized groups, embroiled in their pursuit to force all societies to legitimize and accept their orientation. Notable among these movements was the recent pride movement (LGBTQIA+ rights movement). Similar to preceding equality and freedom movements. The pride movement had encountered multifaceted challenges, including but not limited to stiff resistance from religious institutions. This paper undertakes an incisive analysis of these challenges as it evaluated the strength of arguments for and against these ideologies. Further, this paper aims to examine the moral, religious, scientific, and health implications of both nihilism and LGBTQIA+ approached seeking to reveal the underlying beliefs that shape individuals' understanding of life, identity, and societal norms. Additionally, this exploration intends to uncover intersections and differences in interpretations of various issues, including those related to LGBTQIA+ rights and the philosophy of nihilism, highlighting potential impacts on personal well-being and society as a whole. The study combined primary and secondary sources, encompassing a comprehensive survey research methodology. Employing meticulously crafted questionnaires and interview, we conducted surveys tailored to individuals under 21 and those over 25. This dual-pronged approach aimed to discover potential variations in opinions across age groups. The secondary sources included journal articles, online books and other online materials. In the culmination of our research journey, it found among others that while Nihilism and LGBTQIA+ stand as distinct ideological constructs, both are intricately entwined in the tapestry of self-identity and personal authenticity. It was also found that although, it was significant for individual experiences, self-actualization, pursuit of pleasure, it was paramount and indispensably imperative for these aspirations to be pursued and enjoyed within the bounds of society and sound morality. Society’s role of nurturing, enculturation and internalization but deviant behaviour should be studied for proper understanding, empathy and advising when navigating the intricate nuances of human existence.